Analisis Yuridis Tentang Threshold Pilkada Berdasarkan Putusan MK Nomor 60/PUU-XXII/2024 - Salas, Jevi; Elviandri, Elviandri; Prasetyo, Bayu (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
This study aims to analyze the juridical aspects of the threshold provisions in the Pilkada by referring to the decision. The research method used is a normative research method with a case approach that focuses on analyzing the Constitutional Court Decision Number 60/PUUXXII/2024. The results of the analysis show that the Constitutional Court's decision provides a new interpretation of the threshold provisions, which has the potential to affect the constitutional rights of political parties and independent candidates in the Pilkada contestation. The implication of this decision is a significant change in the regional head nomination mechanism in Indonesia. The General Elections Commission (KPU) revised KPU Regulation Number 8 of 2024 to KPU Regulation Number 10 of 2024 to adjust the nomination regulations with democratic principles and applicable laws. Thus, this decision ensures the legality of regional head candidacy and increases the value of democracy in the 2024 simultaneous regional elections in Indonesia.